Modified Bluegrass Appliance: A Nonpunitive Therapy for Thumb Sucking in Pediatric Patients—A Case Report with Review of the Literature. (22nd May 2013) - Diwanji, Amish; Jain, Preet; Doshi, Jigar; Somani, Prakash; Mehta, Dhaval
Abstract : Oral habits in form of digit/thumb sucking are common phenomenon and part of childhood behavior. They are normally associated with oral pleasure, hunger, anxiety, and sometimes psychological disturbances. Chronic practice can cause major orthopedic alterations to the skeletal structures of the oral cavity and lower face. Aversive approaches in form of punitive therapy have been moderately effective. Modified bluegrass appliance is nonpunitive therapy to treat sucking habits. It acts as a habit reversal technique and installs positive reinforcement in children. Modified blue grass appliance proved to be very comfortable to patients and encourages neuromuscular stimulations.